RUMAH SAKIT PERANG DI GAZA PALESTINA DENGAN PENDEKATAN MOBILE ARCHITECTURE: SURVIVAL UNIT Landasan Konseptual Perencanaan dan Perancangan - , NADIA AGHNIA FADHILLAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The place where now called as Palestine and Israel have very long history of war, the war has been going on since a thousand years BC. After the Balfour Agreement (1917) and Israel's declaration of independence (1948), Israel has destroyed 478 villages out of 585 villages and perform 34 massacre operations of Palestinian civilians. Palestinian fought back with the First Intifada (1987) and the Second (2000). Israeli occupation made Palestine lost almost 90% of its area in the last 65 years. Israeli blockade of air, land, and water of Gaza since 2007 catched Gaza War in 2008, make people of Gazaâs life more difficult. Gaza faces cricists of food, clean water, education, employment, electricity, and health services. With a population of 1.6 million people, Gaza requires 17,760 beds of public hospitals and 12,160 beds of emergency hospital. In fact, even the capacity of all hospitals in Gaza do not meet the 10 per cent of that requirement. War Hospital is urgently needed, as a hospital and also as the center war disaster relief. The needs of Gazaâs people for a hospital will be different to others. The hospital they need is a hospital that dealing directly to the war refugees and the threat of missile that can occur at any time. The hospital that is able to accommodate emergency mass action in the same time so can minimize the number of victims. Hospital that is able to protect itself and their patients from the war. By using mobile architecture as an theory approach then processed with analysis, we got adaptable, compact, and energy independent as major problems that must be solved by War Hospital. Survival Unit were taken as War Hospitalâs design concept to resolve these problems. War Hospital designed to be able to bring basic medical needs for the victims at war. Survival Units are mobile, essential, and livesaver. Keyword: War Hospital, Mobile Architecture, Gaza Palestina, Survival Unit